Characteristics of occupational hazards at the workplace of a nurse - Anna Kowalczyk; Kinga Kulczycka; Ewa Stychno; Beata Chilimoniuk (Kazimierz Wielki University, 2018)
The occupational exposure of nurses is very closely related to the specificity of the place where they carry out their work. Her workplace may be located in health centres, hospital halls, operating theatres, maternity wards, schools, nursing homes, hospices, sanatoriums, and if necessary also in the patient's home. The range of risks that can affect her health and well-being is therefore very wide. It is therefore necessary to identify them precisely and to analyse them thoroughly. The aim of this paper is to present and briefly characterize selected occupational hazards in the position of nurse. The risk of an accident is posed by hazards such as slippery surfaces, electricity, needles, sharp instruments, glass objects, hot appliances, gases and liquids, chemicals, compressed gas, heavy objects or dangerous patient behaviour. In addition to hazardous factors, nurses are also affected by harmful or disruptive factors that lead to illness or well-being. These include stress, shift work, mobbing, infectious material, latex, medicines including cytostatics, electromagnetic fields, UV radiation, ionizing, laser and infrared radiation, cold and hot microclimate, noise, vibrations. The workload of nurses is to a large extent also influenced by ergonomic factors, mainly many hours of work in a forced position and excessive physical effort associated with lifting patients. Each of these risks, if not addressed, not only has a negative health impact in the form of work-related diseases or accidents at work, but also reduces the effectiveness of nurses' work or is a cause of malfunction.